Pengaruh perbandingan jantan-betina dan lama penyimpanan telur terhadap daya tetas telur Burung Puyuh (Coturnix coturnix japonica) - Fatchul Nizar Al Abror; Lisnawaty Silitonga; Satrio Wibowo (Fakultas Peternakan Universitas Kristen Palangka Raya, 2018)
This study was carried out to investigate the effect of breeding sex-ratio eggs storage length, and interaction of both treatments on hatchability of quail eggs. The experiment used Completely Randomized Design with 5x3 factorial patterns, with two replications. The first treatment factor was the variation of sex ratio (1: 1; 1 : 2; 1 : 3; 1 : 4 and 1 : 5), and the second treatment was the eggs storage length (1, 4 and 7 days). The results showed that sex ratio, eggs storage length, and interaction between sex-ratio and eggs storage length has no significant effect on eggs weight, fertility, hatchability and DOQ weight (P> 0,05). In general, the average of egg weight was 10.52 g, fertility of eggs on day 7th was 47.33%, hatchability was 77.28% and DOQ weight was 6.84 g. Keywords : sex-ratio, eggs storage length, hatchability, quail birds.